Rozmowy na koniec wieku 2 - Janowska, Katarzyna; Mucharski, Piotr (Krakow : Wydawn. Znak, 1998)
A collection of intimate interviews with several noted representatives of present day Polish cultural life.
Keywords: Intellectuals -- Poland -- Interviews; Poland -- Intellectual life -- 1989-